The adoption non-adoption dichotomy: Why do smallholder producers dis-adopt improved chicken breeds? - Mulugeta, Yitayih; Kassie, Girma T.; Dessie, Tadelle (2024)
Adopting agricultural technologies is crucial to improve productivity and livelihoods in developing countries. While much research has focused on adoption decisions, understanding dis-adoption, when farmers stop using technology, is equally important. Studies on agricultural technology adoption often treat dis-adopters (those who initially adopted but later discontinued to use) and never-adopters (those who never adopted) as the same, using binary models to analyze farmers’ decisions. We argue that a better understanding of these decisions can be achieved by separately analyzing ’never-adoption’, ’dis-adoption’, and ’adoption.’ Using nationally representative data from three African countries, Ethiopia, Nigeria, and Tanzania, we developed a multinomial logit model to analyze the adoption of improved chicken breeds. Our findings show that dis-adopters of improved chicken are different from never-adopters. Factors associated with dis-adoption include gender and education of household heads, access to training and extension services, breeding and culling practices, access to markets, use of complementary inputs, production objectives, landholding size, income diversity, and access to finance. Policies and strategies that aim to enhance sustained adoption and use of improved chicken breeds should promote a bundle of technologies, including tailored training, women empowerment, locally adapted and farmer-preferred chicken breeds, complementary inputs and services, innovative marketing strategies, and delivery models for bundles of technologies.